Agritourism and local economic development in South Africa - Rogerson, Christian M.; Rogerson, Jayne M. (Bulletin of Geography. Socio-economic Series, 2014)
The role of tourism for local economic development (LED) is a topic of critical importance for geographers. In the case of South Africa tourism is a priority sector for national economic development. The significance of research issues around tourism and LED is underlined by the ‘developmental’ mandate of local governments. Although tourism has received attention in a growing body of LED writings on South Africa issues around agritourism so far have been overlooked. Agritourism represents an evolving form of rural tourism which is targeted at mainly urban consumers. Against the background of a review of international scholarship on agritourism this article explores its potential implications for LED planning in South Africa. A national audit of agritourism is presented which shows its uneven geographical distribution. Agritourism is of special significance for small town economic development in South Africa’s intermediate tourism spaces. Policy suggestions are offered for strengthening agritourism as a driver for LED in South Africa.